Mapping Human Resources to Guide Ophthalmology Capacity-Building Projects in Honduras: Sub-national Analyses of Physician Distribution and Surgical Practices - Rocio Banegas; Luis Rojas; Mariela Castillo; Luis Lagos; Kevin Barber; Britton Ethridge; Sara O'Connor (Ubiquity Press, 2024)
Objective: To map ophthalmologist locations and surgical practices as they vary sub-nationally within Honduras to maximize the impact of efforts to develop cataract surgical capacity. Methods: An anonymous survey was sent to all Honduran ophthalmologists with questions on surgical volume, department-level location, type of facility in which they work, surgical methods, and age. Surgical volume, population, and poverty data sourced through the Oxford Poverty Human Development Initiative were mapped at the department level, and cataract surgical rates (CSR; surgeries per million population per year) were calculated and mapped. Results: Sixty-one of the 102 Honduran ophthalmologists contacted responded. Of those, 85% perform cataract surgery, and 49% work at least part time in a non-profit or governmental facility. Honduras has fewer surgical ophthalmologists per million than the global average, and though national CSR appears to be increasing, it varies significantly between departments. The correlation between CSR and poverty is complex, and outliers provide valuable insights. Conclusion: Mapping ophthalmological surgical practices as they relate to population and poverty at a sub-national level provides important insights into geographic trends in the need for and access to eye care. Such insights can be used to guide efficient and effective development of cataract surgical capacity.